PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KECERDASAN SPASIAL SISWA PADA MATA PELAJARAN GEOGRAFI DI KELAS X IIS SMA NEGERI 7 PADANG - Farisha Luthfi; Surtani Surtani (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This study aims to determine the effect of the Problem Based Learning (PBL) model on Students' Spatial Intelligence in Geography Subjects in Class X-IIS SMA Negeri 7 Padang. This type of research is quasi experimental (quasi experimental design). This research was conducted on students of class X IIS 1 and X IPS 2 in SMA Negeri 7 Padang in the semester July-December 2019. The population was students of class X IIS consisting of 4 classes. The research sample was taken by cluster random sampling technique, so that the X IIS 1 class was obtained as the experimental class and X IIS 2 class as the control class. Data collection through observation, documentation and testing. Data analysis is descriptive statistical analysis and inferential statistics. The results showed that there was an influence of the Problem Based Learning (PBL) model on the Spatial Intelligence of Students in Geography Subjects in Class X-IIS of SMA Negeri 7 Padang. This is based on the results of hypothesis testing conducted, obtained tcount of 4.972 with a significant level (α) 0.05 and (α) 0.01 obtained ttable of 1.665 means that the value of tcount is greater than table.